2008
DOI: 10.4049/jimmunol.180.8.5537
|View full text |Cite
|
Sign up to set email alerts
|

UropathogenicEscherichia coliBlock MyD88-Dependent and Activate MyD88-Independent Signaling Pathways in Rat Testicular Cells

Abstract: Uropathogenic Escherichia coli (UPEC) is the most common etiological cause of urogenital tract infections and represents a considerable cause of immunological male infertility. We examined TLR 1–11 expression profiles in testicular cells and the functional response to infection with UPEC. All testicular cell types expressed mRNAs for at least two TLRs and, in particular, synthesis of TLR4 was induced in testicular macrophages (TM), Sertoli cells (SC), peritubular cells (PTC), and peritoneal macrophages (PM) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(128 citation statements)
references
References 53 publications
(42 reference statements)
2
126
0
Order By: Relevance
“…113 Other NLRs are involved in the processing and activation of inflammatory cytokines, including IL-1b and IL-18, which are activators of inflammasomes. 114 Both NOD1 and NOD2 mRNAs were detected in some testicular cells, including SCs and germ cells, 105 but their functions in these cells have not been examined. Many NLR members are involved in immune modulation as inflammasome activators.…”
Section: Other Prrs In the Testismentioning
confidence: 99%
See 2 more Smart Citations
“…113 Other NLRs are involved in the processing and activation of inflammatory cytokines, including IL-1b and IL-18, which are activators of inflammasomes. 114 Both NOD1 and NOD2 mRNAs were detected in some testicular cells, including SCs and germ cells, 105 but their functions in these cells have not been examined. Many NLR members are involved in immune modulation as inflammasome activators.…”
Section: Other Prrs In the Testismentioning
confidence: 99%
“…84,85 Different stages of germ cells also express TLRs. 105 We recently demonstrated that TLR3 in spermatogonia and spermatocytes and TLR11 in spermatids initiate innate immune responses. 108,109 The TLR-initiated innate immune responses in male germ cells are particularly interesting because the germ cells represent a majority of the testicular cell population.…”
Section: Tlrs In Testicular Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of TLR2-6 mRNA in mouse Sertoli cells and subsequent activation of the NF-kB pathway following stimulation with TLR2 and TLR5 agonists were demonstrated by Riccioli et al (2006). Bhushan et al (2008) demonstrated that all testicular cell types expressed mRNAs of one to six TLRs, and, in particular, TLR3 transcription was evident in all testicular cells, suggesting a strong capacity for the recognition of double-stranded viral RNA in the testes.…”
Section: Discussionmentioning
confidence: 99%
“…It is only recently that expression of TLR 1-11 was shown in total rat testis, epididymis and vas deferens (Palladino et al, 2007) and of TLR 1-9 in human testis samples (Nishimura & Naito, 2005). Riccioli et al (Riccioli et al, 2006) A c c e p t e d M a n u s c r i p t 8 weak expression was evident (Bhushan et al, 2008). This indicates a strong capacity of recognizing double stranded viral RNA in the testis.…”
Section: Toll Like Receptor Expression In the Testismentioning
confidence: 99%